Daratumumab Plus Bortezomib, Melphalan, and Prednisone Versus Bortezomib, Melphalan, and Prednisone in Transplant-Ineligible Newly Diagnosed Multiple Myeloma: Frailty Subgroup Analysis of ALCYONE - Mateos, Maria-Victoria; Dimopoulos, Meletios A; Cavo, Michele; Suzuki, Kenshi; Knop, Stefan; Doyen, Chantal; Lucio, Paulo; Nagy, Zsolt; Pour, Ludek; Grosicki, Sebastian; Crepaldi, Andre; Liberati, Anna Marina; et al. (Clinical lymphoma, myeloma & leukemia, 2021)
BACKGROUND: In the phase 3 ALCYONE study, daratumumab plus bortezomib/melphalan/prednisone (D-VMP) versus bortezomib/melphalan/prednisone (VMP) significantly improved progression-free survival (PFS) and overall survival (OS) in transplant-ineligible, newly diagnosed multiple myeloma (NDMM) patients. We present a subgroup analysis of ALCYONE by patient frailty status. PATIENTS AND METHODS: Frailty assessment was performed retrospectively using age, Charlson comorbidity index, and baseline Eastern Cooperative Oncology Group performance status score. Patients were classified as fit (0), intermediate (1), or frail (≥2); a nonfrail category combined fit and intermediate patients. RESULTS: Among randomized patients (D-VMP, n = 350; VMP, n = 356), 391 (55.4%) were nonfrail (D-VMP, 187 [53.4%]; VMP, 204 [57.3%]) and 315 (44.6%) were frail (163 [46.6%]; 152 [42.7%]). After 40.1-months median follow-up, nonfrail patients had longer PFS and OS than frail patients, but benefits of D-VMP versus VMP were maintained across subgroups: PFS nonfrail (median, 45.7 vs. 19.1 months; hazard ratio [HR], 0.36; P < .0001), frail (32.9 vs. 19.5 months; HR, 0.51; P < .0001); OS nonfrail (36-month rate, 83.6% vs. 74.5%), frail (71.4% vs. 59.0%). Improved greater than or equal to complete response and minimal residual disease (10-5)-negativity rates were observed for D-VMP versus VMP across subgroups. The 2 most common grade 3/4 treatment-emergent adverse events were neutropenia (nonfrail: 39.2% [D-VMP] and 42.4% [VMP]; frail: 41.3% and 34.4%) and thrombocytopenia (nonfrail: 32.8% and 36.9%; frail: 36.9% and 39.1%). CONCLUSION: Our findings support the clinical benefit of D-VMP in transplant-ineligible NDMM patients enrolled in ALCYONE, regardless of frailty status.
Keywords: Male; monoklonální protilátky; CD38; bortezomib; Antineoplastic Combined Chemotherapy Protocols; Aged; Multiple Myeloma; mužské pohlaví; senioři; melfalan; Bortezomib; prednison; senioři nad 80 let; Clinical study; lidé; ženské pohlaví; Efficacy; Humans; protokoly protinádorové kombinované chemoterapie; Frail; Monoclonal antibody; Aged, 80 and over; Prednisone; Antibodies, Monoclonal; mnohočetný myelom; Female; Melphalan